Metabolic subtypes of clear cell renal cell carcinoma defined by tobacco smoking. (4th March 2021) - Czyzyk-Krzeska, Maria F.; Meller, Jarek; Landero Figueroa, Julio A.; Plas, David R.; Cunningham, John T.
ABSTRACT: Tobacco smoking (TS) results in reprogramming of major metabolic pathways, including glycolysis, the citric acid (TCA) cycle, oxidative phosphorylation, and metabolism of aspartate, glutamate and glutamine in clear cell renal cell carcinoma (ccRCC). TS alters the distribution and activities of cadmium, arsenic and copper in a manner mechanistically supporting metabolic remodeling. Alterations in metabolism and metal distribution identify new actionable targets for treatment of ccRCC.